Sexual Assault and Sexual Harassment in the U.S. Military - Morral, Andrew R. (RAND Corporation, 2015)
The Department of Defense Sexual Assault Prevention and Response Office asked the RAND Corporation to conduct an independent assessment of the rates of sexual assault, sexual harassment, and gender discrimination in the U.S. military. This volume presents survey results from the 2014 RAND Military Workplace Study for active- and reserve-component service members in the Army, Navy, Air Force, and Marine Corps.